Krakowska koronka klockowa. Teoria i praktyka niematerialnego dziedzictwa kulturowego .......... 89 - Łukaszewska-Haberkowa, Justyna (Niematerialne dziedzictwo kulturowe w teorii i praktyce, 2021)
THE THEORY AND PRACTICE OF INTANGIBLE CULTURAL HERITAGE The paper describes activities and experiences connected with Kraków bobbin lace which was inscribed on the National List of the Intangible Cultural Heritage in 2016. I will present the issue, indicating current changes and possible solutions. Activities in favour of Kraków bobbin lace as the intangible cultural heritage of Poland are supported by the Museum of Kraków.